Pola bekerja sambilan kalangan pelajar sekolah menengah di daerah Melaka Tengah dan implikasinya terhadap prestasi pembelajaran di sekolah - Noraziah Ali,; Ranimah Yusuf,; Hasnah Ali, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2008)
Fast development in the District of Melaka Tengah, which is closely related to urbanization and globalisation, has generated job opportunities in various economic sectors. Secondary schools students are part of the work force, working part-timely in shopping complexes, food stalls, workshops, factories and others. This study aims to look into the work patterns of secondary school students in the District of Melaka Tengah and the implications on their studies. A total of 126 students, purposively selected from five secondary schools were interviewed in the middle of 2007. The results showed that most of respondents worked parttime in the various service sectors after schools, during weekend leave and during school holidays. By working they faced both time and physical contraints which affect their learning activities after school such as doing homework and revision at home, co-curiculum etc. However, their income from working part-time has helped their family financially besides fulfilling self needs and generating feeling of confidence among them. Many related issues surfaced in this study. Some were forced to work to assist family’s financial needs due to poverty; while others work to buy modern gadgets to fulfill modern lifestyles (such as handphones, brended outfits); but the most critical was they lost focus in their studies. Thus, the phenomenon of working part-time among school students distrupts their studies and may affect their educational performance